Mental Representations of 14-15 Years Old Students about the Light Propagation Time - Ravanis, Konstantuinos; Kaliampos, George (FKIP Universitas Lampung, 2018)
Mental representations of 14-15 years old students about the light propagation time. Objectives: The study of students’ representations of physics concepts and phenomena constitutes a central part of science education research, as they play a decisive role in teaching. In the study presented here, we investigate the mental representations of 14-15 years old students about the light propagation time, before they were taught about it in school. Methods: The empirical data was gathered through an interview using three tasks which involved the evaluation of hypothetical situations. The research data included representations that cause difficulty in the comprehension of the position of a light source in relevance to the light propagation time. Findings: Most of students assumed that the identification of the light propagation time is strongly correlated with the large distance between the light source and the receiver. Conclusion: This study concluded that the arrangement of objects in space strongly influences the students’ thinking. Keywords: Light propagation time, mental representations, 14-15 years old students. DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201806